Enhancing resilience to change: a mobile-learning intervention facilitating the transition from primary to secondary education - Nicolaidou, Despo; Nicolaidou, Iolie (My University, 2023)
The transition from primary to secondary education has been an important issue for students mainly because of the stress caused by sudden changes, which may consequently affect students’ overall well-being and academic performance. Research has shown that many interventions are attempting to facilitate students’ transition to secondary school and help them become more resilient to changes. However, there is a limited number of interventions integrating digital tools. Considering that incorporating technology in the learning process can encourage reluctant students to express themselves anonymously, help students become part of a wider community post-intervention, and support them in developing stress management skills, there is a need for digital integration of interventions aiming at enhancing students’ resilience to changes in their primary-to-secondary transition. This study aims to address this gap identified in the literature and provide answers regarding how technologically supported interventions for facilitating the transition from primary to secondary education may affect students’ mental health, ability to cope with problems, and perceptions about the primary-to-secondary transition. To this aim, a digitally supported intervention was developed based on a selection of existing paper-based activities with tested results for facilitating students’ transition from primary to secondary education. The intervention was enacted through the online platform Nearpod. The activities, which incorporated digital tools, were designed to facilitate children in developing techniques that help them cope with problems caused by changes in their lives and become more resilient. Twenty-five 6th grade primary-school students participated in three eighty-minute lessons of a pre-test post-test experimental study. Data sources included validated questionnaires (administered pre and post) measuring students' (a) mental health (focusing on emotional problems and peer relationship problems) using the Strengths and Difficulties Questionnaire (SDQ-Hel), (b) ability to cope with problems (Coping Self-Efficacy Scale CSES), and (c) perceptions of transition using the Perceptions of Transition Survey (PTS). Students’ mental health was unaffected post-intervention and the intervention was effective only for a small number of students' emotional problems (2/25) and peer relationship problems (2/25). Students’ self-efficacy to cope with problems remained unchanged (Mpre=6.21 out of 10, SD=1.06; Mpost=6.08, SD=1.5). However, after the intervention, students felt more confident in “sorting out what can be changed and what not” (increased by 1.09 points out of 10) as well as “keeping from feeling down” (increased by 0.67 points). These situations were among the statements that students initially reported having the least confidence. Finally, the study revealed that students’ perceptions of problems they may face in their transition remained unchanged. The intervention was effective only with respect to lowering students’ worries about issues of “fitting in” and “getting accepted by other students” which had a significant decrease.
Keywords: Transition; Resilience; Children; Primary to secondary school; Mobile learning; Adapt to change